Entrepreneurship in Islam: Analysis of Principles, Strategies and Concepts of Prophet Muhammad's Success in Trading - Hosen, Hosen; Syaiful Anam; Mohammad Tohir Salam (Ta'amul: Journal of Islamic Economics, 2023)
Entrepreneurship in Islam is the act of buying and selling or exchanging goods or services when there is no money, both on the basis of mutual agreement and not coercion. The disciplined and methodical application of creativity and innovation to the needs and opportunities of trading markets results in entrepreneurship. This includes placing a strategic focus on new concepts and insights, creating and or solving problems, and so on. Being an entrepreneur in the field of trade is an example for humanity as a whole throughout the life of the Prophet Muhammad SAW. The fact that he used the name al-amin is proof that the Prophet Muhammad was considered an extraordinary figure in Arab society because of his credibility. This research was conducted by compiling the library (library reasearch). What is meant by "library research" is the process of compiling through the collection, writing, editing, and categorizing of relevant data and information. The data and information come from various written sources related to marketing, both print and online, including drafting reports, scientific essays, theses and accompanying regulations, encyclopedias and other scientific books.